Pengaruh Metode Pembelajaran SAS (Struktural Analitik Sintetik ) Terhadap Kemampuan Baca Tulis Permulaan Siswa Kelas II SD YPK Inamo Kabupaten Sorong - Astri Nadia Iriyani; Muhammad Faizin; Desti Rahayu (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of the SAS (Synthetic- Structural Analytical) Learning Method on the literacy skills of the second graders of SD YPK Inamo, Sorong Regency. This research is research Pre- Experimentby Design One Group Pretest and Posttest. The population in this study were all second graders in SD YPK Inamo, Sorong Regency, with a sample of second graders, totaling 12 students. The data collection instruments used in this study were observation and tests Performance. The data analysis technique consists of four stages, namely the stages of validity testing, reliability testing, normality testing, and hypothesis testing. The results of the instrument validity test were obtained with an average of 83.75. The results of the reliability test of the instrument items obtained the data Pretest of 0.823 and Posttest 0.683. From the analysis test, the normality test is obtained Shapiro-wilk from the pretest data 0.839 > 0.05 and posttest 0.187 > 0.05, then normal data is obtained from these data. From the analysis of hypothesis testing, it is obtained a sig value (2 tailed) of 0.000 <0.005, then H1 accepted and H0 was rejected, which means that the SAS learning method had an effect on the initial literacy skills of second graders at SD YPK Inamo, Sorong Regency.